Restorative Justice in the Perspective of Islamic Law: A Literature Study on Its Relevance in Modern Society - Andre Aazahria Setiawan; Agus Machfud Fauzi (State Islamic University Datokarama Palu, 2025)
This study aims to examine the concept of restorative justice within the perspective of Islamic law and to explore its relevance to the modern criminal justice system. Using a literature review method, this research analyzes twenty accredited scientific articles published between 2015-2025. The findings indicate that the fundamental values of restorative justice, such as sulh, diyyah, and afw, have long been recognized in the tradition of Islamic law. This approach places emphasis not only on punishment but also on reconciliation, victim recovery, and the reintegration of offenders into society. In the context of contemporary legal practice, restorative justice has the potential to address issues such as excessive criminalization, prison overcrowding, and the declining public trust in legal institutions. However, its implementation requires regulatory support, professional training for law enforcement officers, and the internalization of maqashid sharia values within the national legal system. This study concludes that restorative justice is not only compatible with Islamic law but can also serve as a strategic approach to building a legal system that is more humane and socially just